PEMANFAATAN SERBUK TEMPURUNG KELAPA PADA KOMPOSIT Al2O3-EPOXY - Syafruddin Zohri, Ahmad; Sari, Nasmi Herlina; Sujita, S. (Universitas Mataram, 2013)
The purpose of this research is utilization of coconut shell powder on Al2O3-Epoxy composite so it can be used as an alternative material of brake linings that are enviromentlly friendly. In this research, coconut shell powder is used as a filler on Al2O3-Epoxy composites that are made using hand lay up method. Comparison volume fraction of coconut shell powder and Al2O3 was varied amount 0:40, 10:30, 20:20, 30:10 and 40:0 (%). Adhesive was used is epoxy resin namely amount 60%. Test conducted is wear test. The results showed that utilization of coconut shell powder on Al2O3-Epoxy can be decrease the wear so it can be used as an alternative material of brake linings that are environmentally friendly